REPUTATIONAL RISK MANAGEMENT STRATEGY AT INDONESIAN SHARIA BANK AND MUAMALAT INDONESIAN BANK - Neni Utami; Rokhmat Subagiyo; Binti Nur Asiyah (State Islamic Institute (IAIN) Tulungagung, 2023)
Abstract. BSI and BMI suffered significant losses due to reputational risk. Reputation risks that occur can be properly handled so that losses that arise can be recovered immediately. This study aimed to determine the application of risk management to BSI and BMI and the application of reputation risk to BSI and BMI. The results of this study indicate that BSI and BMI have implemented risk management in accordance with POJK No. 65 of 2016. BSI and BMI have specific organizations to deal with risks, procedures, and the same problem focus on dealing with reputation risk even though the steps for implementing procedures between the two are different. BSI is more focused on strategic steps taken in overcoming risks, while BMI is not only focused on strategic steps taken but also focused on media coverage and communication management.